2019
DOI: 10.1016/j.jid.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Skin Fibrosis in Systemic Sclerosis by Extracellular ATP via P2Y2 Purinergic Receptor

Abstract: Tissue injury/hypoxia and oxidative stress induced-extracellular adenosine triphosphate (ATP) can act as damage-associated molecular pattern molecules, which initiate inflammatory response. Our objective was to elucidate the role of extracellular ATP in skin fibrosis in systemic sclerosis (SSc). We identified that hypoxia enhanced ATP release and that extracellular ATP enhanced IL-6 production more significantly in SSc fibroblasts than in normal fibroblasts. There were no significant differences of P2X and P2Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Also, it was already described that Staphylococcus aureus USA300, one of the most prevalent bacterial species identified in chronic wounds, exploits the immunomodulatory characteristics of ADO to subvert host immune response (50), retarding the healing of infected wounds. Lastly, ADO and ATP also promote fibrosis when released in high concentrations or chronically (51)(52)(53), which denotes a negative aspect in the case of topically application.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was already described that Staphylococcus aureus USA300, one of the most prevalent bacterial species identified in chronic wounds, exploits the immunomodulatory characteristics of ADO to subvert host immune response (50), retarding the healing of infected wounds. Lastly, ADO and ATP also promote fibrosis when released in high concentrations or chronically (51)(52)(53), which denotes a negative aspect in the case of topically application.…”
Section: Discussionmentioning
confidence: 99%
“…P2X receptors are ATP-gated ion channels, and P2Y receptor is a G protein-coupled receptor [47]. We recently identified that hypoxia enhanced ATP release, and extracellular ATP-induced phosphorylation of p38 via P2Y 2 receptor enhanced IL-6 and collagen type I production in SSc fibroblasts [50]. Our previous findings suggested that kaempferol also might inhibit extracellular ATP-induced IL-6/collagen type I production in vivo by the inhibition of ATP:P2Y 2 receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of ATP in the mouse skin was measured using "Tissue" ATP assay kit (TOYO INK) according to the manufacturer`s protocol and the previously described protocols [20].…”
Section: Measurement Of Atp Concentrationmentioning
confidence: 99%
“…There is recent evidence suggesting that extracellular ATP can serve as a damage-associated molecular patterns (DAMPs) molecule that initiates an inflammatory response through autocrine/paracrine signaling [18]. ATP can be released from cells by various stimulators, including mechanical stress, tissue injury, inflammation, and hypoxia [19,20]. Further, in PUs, it is assumed that ATP is released extracellularly by physical and hypoxic stimulation due to skin pressure.…”
Section: Introductionmentioning
confidence: 99%